Costal vein chaetotaxy, a neglected character source in Fanniidae and Muscidae (Diptera: Calyptratae) - Michelsen, Verner (European Journal of Taxonomy, 2022)
The present study examines whether the chaetotaxy of the costal vein in the calyptrate families Fanniidae and Muscidae deserves more attention in phylogenetic and taxonomic contexts. An overview of the macrotrichia and their arrangement on wing vein C is given. Special attention is given to the presence/absence of ventral and dorsal setulae on the costal sectors CS1‒3. This is described as one variable character (A) with nine states (A0‒A8). Specimens of both sexes (when possible) of each species belonging to 4 of a total of 5 fanniid genera and 115 of a total of 179 muscid genus-group taxa were examined and scored for character A. It was found that the presumed ancestral state of character A differs between the two families. It is further shown that the main transformational trend in character A in Muscidae has been bi-directional, leading either to the loss of ventral setulae or the gain of dorsal setulae. The utility of character A in the Fanniidae and Muscidae is many-sided and involves taxa ranging from species to family. It is concluded that character A and other aspects of costal chaetotaxy deserve more attention in morphology-based studies of calyptrate flies.